Analisis Faktor Penentu Profitabilitas Bank Syariah: Studi Literatur - wahyudi, Catur; Bawono, Anton; Wijaya, Juli Riyanto Tri (Institut Keuangan-Perbankan Dan Informatika Asia Perbanas, 2025)
This study aims to explore the influence of Good Corporate Governance (GCG), Financing to DepositRatio (FDR), Capital Adequacy Ratio (CAR), Non-Performing Financing (NPF), and Operating Coststo Operating Income (BOPO) on the profitability of Islamic Commercial Banks in Indonesia, using aliterature study approach. The novelty of this study lies in its approach that integrates variousfundamental factors in Islamic banking. Through analysis of various relevant literature sources, thisstudy is expected to provide a deeper understanding of the factors that influence the profitability ofIslamic financial institutions. The results show that the influence of these five variables on profitabilityis inconsistent, with varying impacts from one study to another. For example, the CAR variable wasfound to have a significant impact on profitability in some studies, while others did not show similarresults. On the other hand, GCG showed a significant negative relationship with Islamic bankperformance, especially on the composition of the Sharia Supervisory Board. This finding can bestrengthened by using the Islamic Performance Index (IPI) approach, which not only measuresfinancial performance, but also aspects of sharia compliance, social responsibility, and distributivejustice. Further research is recommended to add variables such as Net Interest Margin (NIM) andyields, especially for Islamic banks listed on the IDX.